On positive eigenfunctions of one nonlocal boundary problem - Pečiulytė, Sigita; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2023)
In this paper we present separate cases of Sturm–Liouville problem with nonlocal two-point boundary condition. The existence of positive eigenvalues and eigenfunctions is analysed. Obtained results we compare with results that are described in paper [1] and denote that in some cases they don’t coincide.